The Labrador Central Mineral Belt IOCG Province -A Uranium-rich end member of the IOCGU Class - Rick Valenta (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Is the Labrador Central Mineral Belt part of the IOCGU Club? ?I sent the club a wire stating, PLEASE ACCEPT MY RESIGNATION. I DON'T WANT TO BELONG TO ANY CLUB THAT WILL ACCEPT ME AS A MEMBER.? GrouchoMarx Acknowledgements ?Ian Dunlop, Matt Lennox-King, Mark O?Dea, Dave Barbour, Derek Wilton, Lucas Marshall, Roland Butler, Mark King, Sally Howson,